Occupational Health and Safety - An Element of Efficient Business Management - G. Baldermann; Hüttenrauch (Society for Mining, Metallurgy & Exploration, 2005)
Occupational health and safety are an important tool to increase a company’s economic efficiency. The integration of safety-related tasks into the overall structure of entrepreneurial tasks is an inalienable requirement for the sustainable achievement of positive effects. Investments into technical and personnel occupational safety that are tied in a streamlined organizational structure guarantee the improvement of defined indicators. The labor force is of central importance. Its added value ought to be ensured. It is necessary to move away from the employees‘ hazard awareness towards a safety awareness including many other aspects in order to save costs in the long run.